PENINGKATAN HASIL BELAJAR MAHASISWA MELALUI PEMBELAJARAN BERBASIS PROYEK - Sungkono Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2010)
This research aims to improve students’ learning outcome through learning based project on the lecturing of the Development of Audio Media in the Department of Curriculum and Educational Technology School of Education UNY.The type of this research is class action research. The subject of this research is 29 students of Study Program of Educational Technology FIP UNY who are conducting The Development of Audio Media lecturing on academic year 2009/2010. The method of data collection used in this research are test and observation, using the research instrument of test and observation sheet or guidance. The collected data is analised using qualitative descriptive.The research findings show that learning based project could improve students’ outcome on the Development of Audio Media lecturing of Study Program Educational Technology FIP UNY. Moreover, through this research, students become more active in learning process, and the cooperation between students improved significantly.